Assessing the Influence of Greenery on the Behaviour of Road Users1 - Karin Ausserer; Ralf Risser (Transactions on Transport Sciences, 2018)
The share of active mobility in traffic - walking and cycling - can be increased by enhancing of the urban vegetation; this is the core assumption of the Austrian project "GoGreen". The main objective of this research project was to elaborate criteria of the roadside greenery that need to be incorporated into the planning of urban and street spaces, and finally implemented in order to create a highly aesthetic and stimulating atmosphere in public spaces. In addition to literature studies, qualitative methods (expert interviews, focus groups) and quantitative methods (street surveys) were used in this project to identify the needs and wishes of the residents. Subsequently, internal and external workshops helped to design evaluation criteria and recommendations for ordinary measures for promoting and supporting active mobility. In this paper, we focus on the street surveys that allow a glimpse on how citizens perceive the relationship between appropriately set urban vegetation, with respect to safety and attractiveness among other things, and its potential to motivate (more) citizens to walk (more).